Taste aversion as a motivation test of hunger in dairy calves - Woodrum Setser, Megan; Brown, Daniel; Costa, Joao HC; Creutzinger, Katherine (Frontiers in Animal Science, 2025)
Dairy calves frequently experience hunger due to restricted milk allowance and long intervals between meals. Current methods to assess hunger in calves utilize intensive behavioral measures or training of calves for operant conditioning tests, which are generally not suitable for field research. By comparison, feeding a bitter substance to rodents has successfully been utilized to measure animal motivation to access resources, particularly in studies of addiction. Feeding a bitter substance in milk could be adapted to assess dairy calf motivation to drink milk, which could be interpreted hunger. The objectives of these experiments were to determine if 1) calf consumption of milk changed when a bitter substance was added and 2) the addition of a bitter substance to milk could be used to assess hunger in pre-weaned dairy calves. We hypothesized that calves would consume less milk as the concentration of a bitter additive increased and that calves would consume more milk with a bitter additive as the time between meals increased. Twenty-seven individually housed calves (17 Holstein, 10 dairy-beef terminal crosses; 21 ± 3 d of age) were enrolled in 2 Latin Square Design experiments. For each experiment, calves were blocked by breed and sex into one of two treatments: 1) bitter (milk altered with quinine) and 2) control (unaltered milk). In Experiment 1, calves received milk with 0.0, 0.2, 0.3, and 0.4 g/L quinine at their afternoon feeding. In Experiment 2, both bitter (0.35 g/L quinine) and control calves (0.0 g/L quinine) experienced different intervals between meals (6, 12, and 16 h). Milk intake, grain intake, and behavioral measures (time spent drinking, drinking bouts, non-drinking oral behaviors, and aversive behaviors) were recorded during the experimental feeding time for both experiments. Calves in Experiment 1 consumed less milk and performed more non-drinking oral behaviors when it was altered with quinine at 0.4 g/L compared to milk with 0.0, 0.2. and 0.3 g/L. More aversive behaviors (nostril/muzzle lick, lip smack, head bib/swing, and failed attempts to drink milk) were also performed when calves were fed milk with any quinine concentration compared to 0.0 g/L. The reduced milk consumption and performance of more aversive behaviors during the consumption of bitter milk indicates that calves find quinine aversive. Likewise, in Experiment 2, calves in the bitter treatment consumed less milk than control calves regardless of the length of time between meals. No interaction between treatment and feed withhold time was observed on milk intake, indicating calves did not change their willingness to consume bitter milk when feed was withheld for a longer time. However, calves provided unaltered milk performed more drinking bouts when milk was withheld longer, and all calves performed more non-drinking oral behaviors at 12 and 16 h and consumed more starter after longer periods between meals. These changes in behavior support increased hunger in calves despite the lack of difference in bitter milk intake with prolonged periods between meals. In conclusion, these results show that calves altered their consumption of bitter milk when the quinine concentration was greater, and that intake should not be the sole measure to consider when utilizing taste aversion to assess calf hunger.